2016
DOI: 10.1186/s12936-016-1604-z
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of laboratory-confirmed malaria in clinically diagnosed adult women from the Wakiso district of Uganda

Abstract: BackgroundThe malaria burden in sub-Saharan Africa (SSA) has fallen substantially. Nevertheless, malaria remains a serious health concern, and Uganda ranks third in SSA in total malaria burden. Epidemiological studies of adult malaria in Uganda are scarce and little is known about rates of malaria in non-pregnant adult women. This pilot study assessed malaria prevalence among adult women from Wakiso district, historically a highly malaria endemic region.MethodsAdult women using public health services were scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…Different criteria have been used to describe afebrile and febrile infections [24, 25]. However, several studies defined infections similarly to the present study [3, 10, 2428]. Similar gametocyte levels were present in this study.…”
Section: Discussionsupporting
confidence: 60%
“…Different criteria have been used to describe afebrile and febrile infections [24, 25]. However, several studies defined infections similarly to the present study [3, 10, 2428]. Similar gametocyte levels were present in this study.…”
Section: Discussionsupporting
confidence: 60%
“…The observed low prevalence could also be due to the demographic characteristics of our study population. Our study population was an adult population from predominantly urban settings which inherently have a low prevalence of malaria [3, 36]. Further, 20% of the study participants reported a history of malaria treatment in the previous month.…”
Section: Discussionmentioning
confidence: 99%
“…Entebbe has an HIV prevalence of ~ 20% [ 19 ] and a schistosomiasis prevalence of ~ 70%, largely due to S. mansoni [ 19 ] with much lower (< 1%) rates of S. haematobium [ 21 ]. Consenting women aged 18–45 years ( n = 58) attending family planning or child vaccination clinics at Entebbe General Hospital or a nearby General Practice clinic were screened for HIV, malaria and pregnancy as previously described [ 22 ]; those who tested positive for any of the three conditions were referred for appropriate care according to the Uganda clinical guidelines while those testing negative were eligible for enrolment. This study was designed to provide pilot data for future immune studies, therefore no formal sample size calculations were made.…”
Section: Methodsmentioning
confidence: 99%